Supervisor Support on Job Satisfaction and Employee Turnover Intention - Mariam, Siti; Sinaga, Samuel J. (Majalah Ilmiah Bijak, 2024)
This research aims to determine the effect of illegitimate tasks and supervisor support on job satisfaction and turnover intention among PT staff. Sumber Alfaria Trijaya in Tangerang City. Using a type of causality research with a quantitative method approach. The population of this research is PT staff. Sumber Alfaria Trijaya in Tangerang City. The sampling method used was a non-probability sampling method using a purposive sampling technique, with a total sample of 129 Alfamart staff. Data analysis was carried out using SEM-PLS with the help of SmartPLS software. The research results show that illegitimate tasks have no effect on job satisfaction, but have a positive effect on turnover intention. On the other hand, supervisor support has a positive effect on job satisfaction, but has no effect on turnover intention. Apart from that, job satisfaction has a negative effect on turnover intention.